(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
This article is devoted to contemporary motivational systems used in the organization and their specificity in the light of selected problems. The aim of the article is to present contemporary incentive systems in the organization and their specificity in the light of selected problems. The article presents the issue of motivation from the perspective of selected theoretical considerations. The theoretical aspect of the motivation system has been emphasized. The essence of selected modern forms of motivating employees beyond pay in organizations was also presented. The article presents the subsystems of the main incentive system. The functions of the management process were also compared. A research report was presented, presenting the results of the research from the 2018 "People Unboxed" report, which is also the result of ADP’s research and which mentions, among others, the issue of employee motivation.